IMPLEMENTING A CANVAS BUSINESS MODEL IN DWH BILEBANTE AND DWH SESAOT'S TOURISM PACKAGE INNOVATION - Endang Sri Wahyuni; Supardi; IAY Sari Dewi Utami Pidada (International Journal of Social Science, 2021)
Bilebante Green Tourism Village Central Lombok and Sesaot Green Tourism Village are two tourist villages that have the same history in building and developing tourist villages. DWH Bilebante was first initiated for its development by the Putri Renjani cooperative. At the same time, DWH Sesaot was ideated and set for the first time by the Sugeh Engger Sesaot Cooperative. The cooperative has a business unit, DWH, which is tasked with developing tourism businesses to increase cooperative profits. The two DWHs were also facilitated in 2014 by GIZ (Gesellschaft fur Internationale Zusammenarbeit), an institution from Germany whose primary focus is building the Government of Indonesia to develop Tourism Villages. These two villages were significantly impacted by the organization's assistance in developing the village into tourist spots.This study aims to find out how the tour packagesinnovationoccurred at DWH Bilebante and DWH Sesaot. This research describes how to tour package innovations and product designs are carried out using a business model BMC (business model canvas). This research is qualitative. The reference for innovation comes from Law No. 19. Innovation is a research, development, and/or engineering activity carried out to develop the practical application of new scientific values ​​and contexts or new ways to apply existing science and technology into products or production processes.This research was included in the research and development study, and the engineering carried out for the development.So, this study views the process in Research & Development developed by Sugiono (2008:40). It can be used to describe how the tour package innovations were carried out by the two DWHs, Bilebante and Sesaot. The stage starts from finding potential and problems, data collection, product design, design validation, redesign vision, product testing, product revision, product testing, potential and problems, mass production (marketing). The study results are DWH Bilebante, and DWH Sesaot have carried out various tour package innovations but have not implemented BMC (business model canvas) to innovate tour package products.They have stepped up the process without going through product designs made in BMC, so the resulting product has no desirability, feasibility, viability. Thus these two DWHs have not been able to sell tour packages optimally with maximum value.